2012
DOI: 10.1038/pr.2012.42
|View full text |Cite
|
Sign up to set email alerts
|

Maternal weight and excessive weight gain during pregnancy modify the immunomodulatory potential of breast milk

Abstract: IntroductIon: Breast milk is an optimal source of nutrition for infants. It contains bioactive components including bacteria that support the microbial colonization and immune system development of the infant. The determinants of human milk composition remain poorly understood, although maternal nutritional and immunological status as well as lifestyle and dietary habits seem to have an impact. Methods: The subjects selected were women from a prospective follow-up study categorized by BMI. Milk samples were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
2
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(212 citation statements)
references
References 38 publications
7
193
2
10
Order By: Relevance
“…Whilst chorionamnionitis caused by bacteria such as Ureaplasma urealyticum is a recognized risk factor for neonatal morbidities including necrotizing enterocolitis, cerebral palsy and bronchopulmonary dysplasia, it is also becoming widely accepted that nonpathogenic bacteria are present in the placenta and amniotic fluid in healthy, term pregnancies (62). Bacterial DNA is consistently found in meconium suggesting fetal contact with microbes in amniotic fluid (5,8,22). We have recently reported that microbial DNA belonging most commonly to Bifidobacterium spp.…”
Section: Immune Programming and Early Microbial Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst chorionamnionitis caused by bacteria such as Ureaplasma urealyticum is a recognized risk factor for neonatal morbidities including necrotizing enterocolitis, cerebral palsy and bronchopulmonary dysplasia, it is also becoming widely accepted that nonpathogenic bacteria are present in the placenta and amniotic fluid in healthy, term pregnancies (62). Bacterial DNA is consistently found in meconium suggesting fetal contact with microbes in amniotic fluid (5,8,22). We have recently reported that microbial DNA belonging most commonly to Bifidobacterium spp.…”
Section: Immune Programming and Early Microbial Contactmentioning
confidence: 99%
“…In addition, maternal health including conditions such as allergy and obesity may affect milk microbiota, resulting in reduced levels of Bifidobacterium spp. compared to healthy mothers (22,23).…”
Section: Microbial Exposure In Uteromentioning
confidence: 99%
“…We found that preconception BMI was related to decreased levels of the Th2 cytokine IL-13 and Th1 cytokine IFN-γ in whey samples. Surprisingly, only one study investigated the relationship between maternal obesity and breast milk cytokine levels (29). Collado et al found that TGF-β2 and sCD14 levels in the breast milk of overweight mothers were lower than the levels Articles Burch et al…”
Section: Maternal Characteristics and Other Child's Covariatesmentioning
confidence: 99%
“…Of particular interest is how the intestinal microbiota is established, given the potential impact it has on subsequent health and disease (Reinhardt et al, 2009;Scholtens et al, 2012). Patterns of early intestinal colonization can have both short-term and long-term health effects (Bager et al, 2008;Cho et al, 2012;Collado et al, 2012;Kalliomäki et al, 2008;Salvini et al, 2011). Bacterial colonization of the intestine is key in several aspects: bacteria provide essential nutrients for the infant such as vitamins and short-chain fatty acids, they stimulate the development of the immune system, especially adaptive responses, and they provide general protection against pathogen colonization, among several other functions (Hooper et al, 2012;Nicholson et al, 2012).…”
Section: Establishment Of the Infant Intestinal Microbiotamentioning
confidence: 99%